Institusi Pendidikan Islam II: Darul Hikmah, Darul Ilmi Dan Bimaristan - Ismi Fauziah (Hikmah, 2018)
Even Abbasid authority in Baghdad starts weakening, then came the time of disintegration. At the time of the disintegration of this came some little dynasty in its own right and broke away from the authority of the Abbasid Even in Baghdad. Among the small dynasties that separates it is the Fatimid dynasty, Fatimid Dynasty arises in North Africa at the end of the third century CE under the leadership of Ubayd Allah Al-Mahdi Shiite Sect that has Ismailiah. They recognized as a descendant of the Prophet through Ali and further through the lineage Fathimah Ishmael the son of Ja'far Al-Sidiq. Darul ilmi is a library founded by Harun Al-Rashid who was the biggest library in it also provided a place of learning spaces. Fatimid dynasty inidi the library has a role that is not small compared to the mosque in the spread of Shia creed Ismailism in society. in the month of jumadil end of 395 Ah/1005 M, on the advice of the Prime Minister Jacob Ibn Killis, Caliph al-hakim founded the Jamiah ilmiyah form Academy (Research Institute) like the other Academies are there in bangdad, Bimaristan has a form of architecture is very unique and spacious, with running water under the floor-the floor. The flowing water serves to cool the room and simultaneously gives freshness. So give peace of mind to patients. Then, the bimaristan already equipped with pharmacies, drugs are referred to with the term "Syarabikhanah" and is headed by a Chief Pharmacist named Sheik. While head of the bimaristan was known by the term "Sa'ur". In every room there are heads of section which carries some according to their respective fields.